CHATTING ABOUT MARRIAGE WITH FEMALE MIGRANTS TO SYRIA. Issue 2 (1st April 2016) - Navest, Aysha; de Koning, Martijn; Moors, Annelies
Abstract : The increasing number of women migrating to Syria from Europe has not only drawn the attention of the media and the security forces but also of researchers. Publications often either undervalue or overvalue women's agency, presenting them as victims of unscrupulous men or foregrounding their militant activism. As many authors work in the field of radicalisation and terrorism studies and use public online posts, they focus on the more radical, activist women who are keen to present themselves to the world at large. In our research project we work with a different focus and employ a different method. Our interest in how these women arrange their marriages and our use of private chatting produces other kinds of knowledge. In contrast to what labels such as 'jihadi brides' suggest, the women themselves desire to live under IS rule, while IS increasingly regulates these marriages. Rather than desiring to become female fighters or recruiting others, they see themselves as responsible for domestic life and attempt to normalize life under IS rule.